Exclusive Data Protection Mechanism: International Experience and Legislation of the Republic of Kazakhstan - Nurtay, M.N.; Sairambaeva, Zh.T. (Bulletin of the Karaganda University “Law Series”, 2022)
One of the indisputable conditions in the development of innovation is the protection of intellectual property rights. The world community develops and effectively applies a collection of means and methods of such protection. Ensuring the existing intellectual property rights in the field of circulation of medicines is a complex of the most complex norms. A distinctive feature of this complex is the inclusion in the legislative norms of ensuring the exclusivity of data on medicines. The purpose of the study is to analyze the exclusivity of these medicines, identify its relevant aspects, and prepare recommendations related to the improvement of legislation and practice in this area. The study reviews the course of application and legal regulation of data exclusivity in relation to drug developers in the European Union (EU), the Eurasian Economic Union (EAEU), the USA. In addition, the legal regime of data protection is analyzed in accordance with the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS), the founder of the World Trade Organization (WTO). The imperfection of the legislative base of the institute of data exclusivity may restrain the development of a judicial practice that has arisen in this area. Based on the analysis of positive and negative trends in the development of exclusivity of these medicines in the Republic of Kazakhstan, the study concludes that it is necessary to improve the legal mechanisms for implementing state policy in this area of intellectual property protection.